A digital vision chip specialized for high-speed target tracking. - Komuro, T. (IEEE Transactions on electron devices)
This paper describes a new vision chip architecture for high-speed target tracking. The processing speed and the number of pixels are improved by hardware implementation of a special algorithm which utilizes a property of high-speed vision and introduction of bit-serial and cumulative summation circuits. As a result, 18 objects in a 128 × 128 image can be tracked in 1 ms. Based on the architecture, a prototype chip has been developed; 64 × 64 pixels are integrated in 7 mm square chip and the power consumption for obtaining the centroid of an object per every 1 ms is 112 mW. Some experiments are performed on the evaluation board which is developed for evaluation under the condition of actual operation. High-speed target tracking including multitarget tracking with collision and separation has successfully been achieved.